In vitro shoot regeneration of Milicia excelsa (Welw.) C.C. Berg - Afolabi, James Oluwaseun; Alagbe, Olajumoke Ayomikun; Oyediran, Rofiat Ifeoluwa; Olomola, Donald Babatope (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2022)
The need for mass propagation and genetic breeding of tree species with economic importance, such as Milicia excelsa, requires an in vitro regeneration protocol. Different concentrations of Gibberellic acid (GA3) (0, 1, 2, 3 and 4 mg/L) and 6-benzylaminopurine (BAP) (0.0, 0.5, 1.0, 1.5 and 2 mg/L) were added to Murashige and Skoog medium for seed germination and shoot regeneration of the species. The treatments were laid out in completely randomised design. Each set of GA3 and BAP treatments were composed by 20 and 6 replicates, respectively. Observations made on cultured seeds include germination percentage at 4 weeks interval while shoot length, number of shoots, number of roots and leaves collected on regenerated shoots at 2 weeks interval were subjected to analysis of variance and means separated with Fisher’s protected Least Significant Difference (L.S.D) at p ≤ 0.05. Results showed that using GA3 positively influenced the seed germination as early germination occurred in the media with GA3, in comparison to the treatment without plant growth regulator (control). Nonetheless, 2.0 mg/L GA3 was observed to be the optimum, having the highest germination percentage of 30% at 4 Weeks after Inoculation (WAI). The results of the BAP effects on the shoot regeneration showed that 0.5 mg/L was the optimum for best shoot growth, having the average number of leaves (6.5), axillary shoots (1.8) and highest shoot length (3.75 cm) in comparison to the control treatment. In conclusion, these results provide insight on in vitro propagation of Milicia excelsa and the techniques employed could be adopted for its shoot multiplication. Index terms: In vitro seed germination; micropropagation; multiple shoots; moraceae.